Low density, three-dimensionally interconnected carbon nanotube/silicon carbide nanocomposites for thermal protection applications. Issue 1 (January 2021) - Aly, Karim; Lubna, Mostakima; Bradford, Philip D.
Graphical abstract: Abstract: Synthesis of silicon carbide (SiC) nanostructures and their composites has been a topic of interest for the scientific community due to the unique properties that can be obtained with nanoscale features. Herein, we report the scalable fabrication of anisotropic and low density, carbon nanotube/SiC (CNT/SiC) core-shell structures synthesized via chemical vapor infiltration (CVI) of silicon on aligned CNT foams followed by heat treatment at 1350 °C. Structures made of CNT/SiC nanotube networks with a thickness of 1 cm and length of 9 cm were prepared in the present work. Upon the removal of the CNT foam via calcination of the hybrid nanocomposite in air, a free-standing mechanically robust three-dimensional network of pure SiC nanotubes was left behind. The density of the synthesized CNT/SiC is the lowest reported for any C/SiC structure. Furthermore, the CNT/SiC hybrid nano-architecture demonstrated superb heat resistance and stability in ultrahigh temperature environment.